The Potential for Great Barrier Reef Regional Climate Regulation via Dimethylsulfide Atmospheric Oxidation Products - Swan, Hilton B. (Frontiers in Marine Science, 2022)
Research related to the potential for coral reef-derived dimethylsulfide (DMS) oxidation products to regulate the regional climate of the Great Barrier Reef (GBR) according to the CLAW hypothesis is summarized in this mini review. The GBR has been indicated as a region of high DMS production where atmospheric emissions may be increased when corals are subject to environmental stresses associated with low tide. During low wind speeds over aerially exposed coral reefs, plumes of atmospheric DMS and new sulfate-containing nano-particle production under photo-oxidative conditions have been detected on the GBR. Hygroscopic growth of these particles in combination with coagulation and condensation processes could potentially provide a coral-mediated mechanism of new aerosol for seeding low-level stratocumulus clouds. Fine mode aerosol optical depth over GBR coral reefs has been correlated with low wind speeds and a coral stress metric formulated as a function of irradiance, water clarity, and tide height. This correlation has been proposed as a possible mechanism by which the GBR might alter the optical properties of the overlying atmosphere to attenuate local insolation leading to regional climate regulation. However, recent regional-scale aerosol-climate modeling indicates that the potential for GBR regional climate regulation via DMS atmospheric oxidation products is weak under current anthropogenic conditions which have instigated mass coral bleaching events along the entire length of the GBR between 1998 and 2022. This increased bleaching indicates that DMS oxidation products are insufficient to regulate the regional climate of the GBR according to the CLAW hypothesis under current global warming conditions.